Analisis Toxic Behavior Dalam Komunikasi Interpersonal Pada Pemain Game Online Mobile Legends: Bang-Bang - Enricco Alend Tribuono; Nunik Hariyani; Zulin Nurchayati (Universitas Merdeka Madiun, 2024)
Mobile Legends Online Game: Bang Bang (MLBB) is an online game with the MOBA (Multiplayer Online Batlle Arena) genre. By presenting a competitive 5 vs 5 match so that this game is loved by many gamers. The online game Mobile Legends: Bang – Bang has chat and voice features to communicate with other players. With various easy to access communication features such as Chat and Voice, this is finally misused for several reasons. Mobile Legends is a team game, so cooperation and coordination between teammates is needed to achieve the goal of this game, which is to destroy the last tower of the enemy. The Chat and Voice features in Mobile Legends are used by players to coordinate with each other. This feature is not only useful as a means of coordination, but also has the potential to be a toxic tool, especially with the intensity of playing hours that are quite high by the players. Although in reality when playing the game Mobile Legends: Bang-Bang directly or face to face, there are also those who behave toxicly with their fellow teams. This research begins with the formulation of the problem of how toxic behavior in interpersonal communication in online game players Mobile Legends: Bang-Bang. The method in this study uses a qualitative approach with research informants totaling 10 players from each epic rank or tier in the Mobile Legends game: Bang-Bang. In the results of this study, there is an interaction between players in the online game Mobile Legends: Bang-Bang both virtual and in person. For virtual communication, the toxic perpetrator conveys a message to the toxic victim and this victim has the right to reply to the message or leave the message and both the victim and the toxic perpetrator have the same position to send and receive messages. As a result, toxic behavior occurs, such as retaliating with toxic cursing behavior, doing Trolls and Feeders, and even AFK. Toxic behavior in the Mobile Legends game is also included in the strategy to get victory by breaking the opponent's concentration to focus on chat. Meanwhile, toxic to teammates has the aim of motivating them to play games to be better than before and as entertainment motivation. While direct communication or face to face, toxic perpetrators convey messages to toxic victims who are friends verbally. Even though he received unpleasant treatment, the informant continued to play with his toxic friend, who valued friendship more than games. This is where the role of the toxic help center provided by Mobile Legends: Bang-Bang. Everyone who reports toxic actions will have their identity protected and those who commit toxic behavior will receive a penalty in the form of a reduced credit score according to what was done in the game